Effects of a pre-workout supplement on hyperemia following leg extension resistance exercise to failure with different resistance loads. Issue 1 (26th September 2017) - Martin, Jeffrey S.; Mumford, Petey W.; Haun, Cody T.; Luera, Micheal J.; Muddle, Tyler W. D.; Colquhoun, Ryan J.; Feeney, Mary P.; Mackey, Cameron S.; Roberson, Paul A.; Young, Kaelin C.; Pascoe, David D.; DeFreitas, Jason M.; et al.
Abstract: Background: We sought to determine if a pre-workout supplement (PWS), containing multiple ingredients thought to enhance blood flow, increases hyperemia associated with resistance training compared to placebo (PBO). Given the potential interaction with training loads/time-under-tension, we evaluated the hyperemic response at two different loads to failure. Methods: Thirty males participated in this double-blinded study. At visit 1, participants were randomly assigned to consume PWS (Reckless™) or PBO (maltodextrin and glycine) and performed four sets of leg extensions to failure at 30% or 80% of their 1-RM 45-min thereafter. 1-wk. later (visit 2), participants consumed the same supplement as before, but exercised at the alternate load. Heart rate (HR), blood pressure (BP), femoral artery blood flow, and plasma nitrate/nitrite (NOx) were assessed at baseline (BL), 45-min post-PWS/PBO consumption (PRE), and 5-min following the last set of leg extensions (POST). Vastus lateralis near infrared spectroscopy (NIRS) was employed during leg extension exercise. Repeated measures ANOVAs were performed with time, supplement, and load as independent variables and Bonferroni correction applied for multiple post-hoc comparisons. Data are reported as mean ± SD. Results: With the 30% training load compared to 80%, significantly more repetitions were performed ( p  < 0.05), but there was no difference in total volume load ( p  > 0.05). NIRS derived minimum oxygenated hemoglobin (O2 Hb) was lower in the 80% load condition compared to 30% for all rest intervals between sets of exercise ( p  < 0.0167). HR and BP did not vary as a function of supplement or load. Femoral artery blood flow at POST was higher independent of exercise load and treatment. However, a time*supplement*load interaction was observed revealing greater femoral artery blood flow with PWS compared to PBO at POST in the 80% (+56.8%; p  = 0.006) but not 30% load condition (+12.7%; p  = 0.476). Plasma NOx was ~3-fold higher with PWS compared to PBO at PRE and POST ( p  < 0.001). Conclusions: Compared to PBO, the PWS consumed herein augmented hyperemia following multiple sets to failure at 80% of 1-RM, but not 30%. This specificity may be a product of interaction with local perturbations (e.g., reduced tissue oxygenation levels [minimum O2 Hb] in the 80% load condition) and/or muscle fiber recruitment.